A clinical review of 38 cases of cervical tuberculous lymphadenitis in Japan – The role of neck dissection. Issue 6 (December 2016) - Omura, Sayaka; Nakaya, Muneo; Mori, Ayumi; Oka, Mineko; Ito, Akiko; Kida, Wataru; Inayoshi, Yasuhiro; Inoue, Aki; Fuchigami, Teruhiko; Takamori, Mikio
Abstract: Objectives: After tuberculous pleurisy, lymphadenitis arising from cervical lesion is the second most common form of extrapulmonary tuberculosis. It is generally treated with antituberculosis agents, but some patients resist chemotherapy. In such cases, surgical resection is often considered as an alternative treatment. This study aims to evaluate the therapeutic outcome of cervical tuberculous lymphadenitis and the future course of treatment of this disease. Methods: We retrospectively reviewed the clinical charts of patients diagnosed at the Tokyo Metropolitan Tama Medical Center between 2009 and 2015 and identified 38 cases of cervical tuberculous lymphadenitis. Precisely 798 patients were registered for primary tuberculosis at our institution during the same period. Results: Patient ages ranged from 21 to 85 years (average: 58.9 years), and the male-to-female ratio was 1:1.2. The range of tuberculosis progression was as follows: 30 (78.9%) in only the cervical lymph node, 3 in the other (axillary, mediastinal, and abdominal) lymph nodes, 1 in the lung and vertebrae lumbales, 2 in the lung, and 1 in the pleural membrane. All 38 patients were initially treated with antituberculous drugs at the Department of Pulmonary Medicine based on guidelines for tuberculosis cases in Japan. In seven cases, the antituberculous drugs were replaced due to side effects. Four cases involved a single drug-resistant strain, and one case involved a double drug-resistant strain. Thirty-three (86.8%) cases were cured by chemotherapy alone. The three patients resistant to chemotherapy were successfully treated through neck dissection. Thirty-six cases (94.7%) were cured by chemotherapy or chemotherapy and surgery. Conclusion: Local therapy could prove effective in cervical tuberculous lymphadenitis patients who exhibit an inadequate response to drugs. The role of neck dissection in cervical tuberculous lymphadenitis remains an important consideration.